A Comparative Randomised Controlled Parallel Group Study Of Maternal, Fetal And Neonatal Outcomes Of Labetalol Versus Methyldopa In The Treatment Of New Onset Hypertension During Pregnancy - REENA VERMA; KINGSHUK LAHON; SD TONPAY; VRUNDA JOSHI KALE (International Journal of Pharma and Bio Sciences, 2012)
Hypertensive disorders in pregnancy remain one of the major causes of maternal and perinatal mortality in developing as well as developed countries and can result in hospital admission, pre-eclampsia and possible premature delivery besides other complications to the fetus and neonate. Antihypertensive drugs are often used to lower blood pressure to prevent this progression to adverse outcomes for the mother and the fetus. Hence, we wanted to compare the maternal, fetal and neonatal outcomes of antihypertensive drugs - labetalol versus methyldopa in pregnancy induced hypertension (PIH) in an Indian population. We carried out a prospective randomised controlled parallel group study on 90 outpatients as well as inpatients of the antenatal ward of Obstetrics and Gynaecology department of our tertiary care teaching hospital. Pregnant patients (20-40 weeks gestational age) newly diagnosed with blood pressure of ≥140/90mmHg and singleton pregnancies with vertex presentation were included in the study. 45 patients each were randomised to either of the two treatment arms – oral methyldopa or oral/IV labetalol. Difference in maternal and fetal/neonatal outcome measurements pre- and post-treatment (on 8th day) were analysed by applying paired‘t’ test. For inter group analysis, we applied chi-square test, using Epi Info statistical software version 3.3. A P-value < 0.05 was regarded as significant with 95% confidence limits. Significantly better maternal outcomes on proteinuria, blood urea, platelet count were seen with labetalol than with methyldopa, but not for rates of spontaneous labour and normal vaginal delivery which were higher with methyldopa. Hypertensive crisis and eclampsia occurred in both groups, without significant difference between groups. There was no significant difference between groups for any of the fetal and neonatal outcomes - stillbirth, death in first week, birth weight, pre-term delivery, Apgar score, need for intensive neonatal care, jaundice, hypoglycaemia and neonatal bradycardia, but incidence of RDS was significantly lower in labetalol group. So, labetalol is comparable to methyldopa in treating and preventing adverse maternal, fetal and neonatal outcomes in new onset hypertension during pregnancy.